2016
DOI: 10.1016/s0140-6736(16)31893-1
|View full text |Cite
|
Sign up to set email alerts
|

Screening and brief intervention for obesity in primary care: a parallel, two-arm, randomised trial

Abstract: SummaryBackgroundObesity is a common cause of non-communicable disease. Guidelines recommend that physicians screen and offer brief advice to motivate weight loss through referral to behavioural weight loss programmes. However, physicians rarely intervene and no trials have been done on the subject. We did this trial to establish whether physician brief intervention is acceptable and effective for reducing bodyweight in patients with obesity.MethodsIn this parallel, two-arm, randomised trial, patients who cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
289
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(302 citation statements)
references
References 30 publications
9
289
0
4
Order By: Relevance
“…Aveyard et al (2016a) found that a brief intervention, where weight was raised as an issue and then a referral to a commercial weight management program was offered, resulted in greater weight loss (mean difference 1.43 kg; 95% CI: 0.89-1.97) than solely raising the issue of weight. This study was important as it was part of routine care where patients were not consulting their GP about their weight, whereas other trials invite patients to take part and only the most motivated respond.…”
Section: Commercial Weight Management Referral Ukmentioning
confidence: 99%
See 1 more Smart Citation
“…Aveyard et al (2016a) found that a brief intervention, where weight was raised as an issue and then a referral to a commercial weight management program was offered, resulted in greater weight loss (mean difference 1.43 kg; 95% CI: 0.89-1.97) than solely raising the issue of weight. This study was important as it was part of routine care where patients were not consulting their GP about their weight, whereas other trials invite patients to take part and only the most motivated respond.…”
Section: Commercial Weight Management Referral Ukmentioning
confidence: 99%
“…This study was important as it was part of routine care where patients were not consulting their GP about their weight, whereas other trials invite patients to take part and only the most motivated respond. The patients in the brief intervention trial are likely to be less motivated than other trial participants and they still lost~2.5 kg at 12 months (Aveyard et al 2016b). The model of care for this intervention involves the GP or patient raising weight management and then the GP offering options for referral to a commercial weight management program.…”
Section: Commercial Weight Management Referral Ukmentioning
confidence: 99%
“…The importance of supportive health care delivery with obese patients has been highlighted very recently, particularly with respect to motivation and adherence to primary care interventions. 36 …”
Section: Exercise and Healthy Consumption As Medicinementioning
confidence: 99%
“…Pharmacists are already involved in providing weight management programs, 9 but there is insufficient evidence to demonstrate their effectiveness, 10 and the contribution they make to tackling obesity warrants further exploration. 11 There is evidence that family physician-led screening and brief motivational advice are effective, 12 and there is no reason why pharmacists working in the community could not also deliver such a structured service, giving priority to overweight patients with conditions exacerbated by obesity (e.g., type 2 diabetes and osteoarthritis). As with smoking cessation progams, pharmacists can effectively deliver lifestyle change interventions, allowing physicians to focus on more complex clinical aspects of obesity.…”
mentioning
confidence: 99%